(3GdWQjb Edi GdSYGOIs - (3YcGTI, CMeOs ((3GdbGgQIs (3GdcQeI ddfTQ hGdJhRjYs, 2015)
(3eaghe GdSYGOI (B-(3eaQMGJ GdfahS GdQHGfjI(B- (3MdGhI GdCed (B- (3LhOIGdMjGI (B-(3GdUMI GdfaSjI (B- (3GdeRGL hLgGR GdefGYI (B=(3Gdfhc hGdCMdGe (B- (3GdJZdH Ydi JYGSI GdeTGcd GdLfSjI ef NdGd GdehSjbi (B-(3GdGjeGf hGdUMI GdfaSjIs
(3eJhaQ GdWHYI GdKGdKI dYGe (B2015 (3HecJHI eUQ GdYGeI (B- (3aQY GdRGhjI GdMeQGAs
(3eJhaQ GdWHYI GdQGHYI dYGe (B2015 (3HecJHI eUQ GdYGeI (B- (3aQY GdRjJhfs
(3eJhaQ ef GdcJGH GdWHYI (B11 (3HecJHI eUQ GdYGeI (B- (3aQY YRHI GdHQLs
1 2 3 4 6 9 11 13 20 21 24
APPLIED_SC
Keywords: (3GdGcJFGHs; (3GdJaGDds; (3GdSYGOIs; (3GdUMI GdfaSjIs; (3GdYdGL HGdehSjbis